2020
DOI: 10.1016/j.jhealeco.2019.102252
|View full text |Cite
|
Sign up to set email alerts
|

The causal effect of education on chronic health conditions in the UK

Abstract: We study the causal impact of education on chronic health conditions by exploitng two UK education policy reforms. The first reform raised the minimum school leaving age in 1972 and affected the lower end of the educational attainment distribution. The second reform is a combination of several policy changes that affected the broader educational attainment distribution in the early 1990s. Results are consistent across both reforms: an extra year of schooling has no statistically identifiable impact on the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…For the sake of comparison, we also estimate the effects of education on average health. A number of studies have exploited changes in compulsory schooling laws to study such effects (e.g., Lleras-Muney 2005;Albouy and Lequien 2009;Silles 2009;Powdthavee 2010;Kemptner et al 2011;Clark & Royer 2013;Jürges et al 2013;Davies et al 2017;Janke et al 2018;Meghir et al forthcoming). We find that staying in school until age 16 reduces body size by 0.15 of a standard deviation and increases blood pressure by 0.15 of a standard deviation, but these estimates are only significant at the 10% level.…”
mentioning
confidence: 99%
“…For the sake of comparison, we also estimate the effects of education on average health. A number of studies have exploited changes in compulsory schooling laws to study such effects (e.g., Lleras-Muney 2005;Albouy and Lequien 2009;Silles 2009;Powdthavee 2010;Kemptner et al 2011;Clark & Royer 2013;Jürges et al 2013;Davies et al 2017;Janke et al 2018;Meghir et al forthcoming). We find that staying in school until age 16 reduces body size by 0.15 of a standard deviation and increases blood pressure by 0.15 of a standard deviation, but these estimates are only significant at the 10% level.…”
mentioning
confidence: 99%
“…Davies et al (2018) further showed that the reform significantly reduced blood pressure, diabetes, heart attack risk, body mass index, sedentary and unhealthy behaviors. However, not all studies show positive effects of the 1972 reform on health and health behaviors and knowledge (Clark and Royer, 2013;Silles, 2009;Janke et al, 2020;Johnston et al, 2015). For example, Jürges et al (2013) have not found any effect on self-rated health and some biomarkers, such as level of fibrinogen and C-reactive protein.…”
Section: The 1972 Educational Reform In England and Walesmentioning
confidence: 99%
“…The education‐health nexus is one of most recognized and documented topics in the field of social sciences. Since the seminal paper of Grossman (1972), the literature on the subject has grown and expanded rapidly (Albarrán et al ., 2020; Avendano et al ., 2020; Janke et al ., 2020). While numerous studies have attempted to investigate this relationship, it remains ambiguous regarding whether education really improves health.…”
Section: Introductionmentioning
confidence: 99%